Investigating the Role of Students’ Attainment, Aptitude and Attitude Assessments in Predicting SAT Achievement: The Case of US-Curriculum Schools in the UAE - HADI, LAMES ABDUL (2021)
The focus on the role of assessments in predicting students’ performance is rapidly increasing. The literature highlights the need to investigate students’ achievement predictors in exit assessments. Some studies have focused on investigating the relationship and/or predictability between one or two types of assessment within the academic, cognitive, or affective domains (Chen et al., 2012; Donati, Meaburn & Dumontheil, 2019; Gonzalez, 2015; Hong, 2018). In US-curriculum schools in the United Arab Emirates (UAE), three types of assessment are implemented that measure students’ attainment, aptitude, and attitudes toward learning, namely the Measures of Academic Progress (MAP), Cognitive Ability Test (CAT4), and the Pupil Attitudes toward Self and School (PASS). The current study utilised those assessments to investigate the role of students’ attainment in MAP, aptitude level in CAT4, and attitude towards learning in PASS assessments in Scholastic Assessment Test (SAT) achievement. This study used an explanatory sequential mixed-method design, and data was collected in two phases. Assessment data of students in Grades 9-12 from five US-curriculum schools in the UAE conducting the MAP, CAT4, PASS, and SAT was analysed to find the relationship between those assessments and to investigate the predictability of SAT using MAP, CAT4, and PASS scores. As a result, in phase one of the study, 603 SAT-Math scores and 169 SAT-English scores for the same students were analysed, and stakeholders’ perceptions were collected from 84 leaders’ and teachers’ and 797 students’ questionnaires dedicated to each participant group. In phase two, 13 leaders, 15 teachers, 32 students, and eight parents were part of focus group interviews. The results highlighted a positive relationship between SAT-Math and SAT-English scores and attainment, aptitude, and the majority of attitudes toward learning factors. Specifically, the strongest positive relationship is between students’ MAP and SAT scores and between CAT4 and SAT-Math. Two prediction equations were developed, concluding that MAP, CAT4, and PASS variables explained 44.7% of the variance in SAT-Math scores with an effect size of 0.808, and 42.9% of the variance in SAT-English scores with an effect size of 0.751. Stakeholders’ perceptions revealed an overall high agreement on the role of students’ academic attainment in English and math, aptitude level, and attitudes toward learning in predicting SAT achievement. Learner self-regard and confidence in learning are the only attitude factors that all stakeholders agreed on in relation to their role in SAT achievement, confirmed by assessment data analysis. Stakeholders’ perceptions highlighted the use of MAP, CAT4, and PASS assessments to support teaching and learning processes and pointed to the lack of a systematic process using assessment data to predict students’ SAT scores. The study contributes to the field by guiding researchers and educators in their pursuit of identifying factors within academic, cognitive, and affective domains that predict students’ academic achievement. Accordingly, the findings can guide educators and schools in supporting students’ academic and social development by finding a systematic process of utilising assessment information, tracking students’ progress, providing feedback about curriculum development, assessment policies, teaching and learning processes, and finally identifying stakeholders’ need for support in the role and use of assessments.